Karakteristik peternak ruminansia di Binjai dan Bahorok, Sumatera Utara - Ma'arif, Ikhwan; Dewi, Rita Rosmala; Sihombing, Juli Mutiara (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Farmer characteristics are one factor influencing the productivity and development of livestock businesses. This research aims to determine the characteristics of ruminant breeders (cattle, sheep and goats) based on demographic factors in Binjai and Bahorok, Langkat Regency, North Sumatra Province. This research is qualitative descriptive research that used a survey method, which was carried out in May - June 2024. The research respondents were 75 surveyed from two city districts: Binjai and Bahorok. The characteristics of the breeders studied were the age of the farmers, the farmer's gender, the length of time they have been farming, the level of education, and the number of livestock cultivated. The data analysis technique used in this research is descriptive qualitative percentage analysis. The results showed that the majority of breeders were aged 31-50 years (65.3%), were male (97.3%), had been farming for more than 5 years (56%), had an education level of up to high school (73.3%), and the number of livestock kept 2 - 5 heads (27.3%). It can be concluded that beef cattle breeders in Binjai and Bahorok District are of a productive age, and the amount of livestock kept is still small.